Orientasi dan Implementasi Career Diamond dalam Bimbingan dan Konseling Karier - Amirullah, M; Zulfikri, Zulfikri; Aswar, Aswar (Indonesian Journal of School Counseling: Theory, Application, and Development, 2023)
Self awareness and world of work awareness are two important keys in career path. Understanding self awareness and world of work awareness can be an important key for someone to plan and direct their career based on their own potential and their environment. Career diamonds are tools that can be utilized by guidance and counseling teachers in providing an overview of the right career direction for students by paying attention to self awareness and world work awareness. The aim of this research is to provide an understanding and alternative media guidance and career counseling that can be used by counseling teachers. The method used is a literature study by examining various sources and references related to career diamonds in the context of career guidance and counseling. The results of the study show that career diamond is an alternative model in career guidance and counseling carried out in schools.